ANALISIS NILAI TAMBAH PENGOLAHAN JAMUR TIRAM MENJADI JAMUR KRISPY PADA PETANI JAMUR DI KAMPUNG MELAYU KOTA BENGKULU - Afriani, Ririn (University of Prof. Dr. Hazairin, SH, 2024)
Mushrooms are natural resources with great potential in the food and agribusiness sectors. Their high nutritional content, low fat, and variety of types make mushrooms highly valuable as a food ingredient. Additionally, mushrooms can be produced at relatively low costs, making them an attractive commodity for development in the agricultural sector. One increasingly popular processed product is crispy mushrooms.The purpose of this research is to analyze the value-added of crispy mushrooms. The research location was purposively determined in Kampung Melayu, Bengkulu City, considering that there is mushroom cultivation and processing of crispy mushrooms in that area. The sample used in this study consisted of farmers from